Persistent strabismus after cataract extraction - Dujić Mirjana P.; Misailović Katarina R.; Kovačević Milena M. (Vojnosanitetski Pregled)
Background. Transient ocular misalignment as a complication of parabulbar and peribulbar anesthesia has already been reported in the literature. The aim of our study was to present a case of irreversible iatrogenic vertical strabismus after cataract surgery, which had to be operated on. Methods. Clinical and orthoptic evaluation of a female patient with vertical diplopia after phacoemulsification cataract surgery. Results. One week after the uneventful surgery, a 68-year-old patient complained of a sudden vertical deviation in the operated eye. The patient had not had a history of previous motility disorders. On examination, the patient showed hypertropia in the left eye of 15−20 degrees in primary position. Three and 6 months postoperatively, there was no a spontaneous improvement, while the persistent vertical deviation was 40 prism dioptres. Strabismus surgery was required 1 year after the cataract surgery. Conclusion. Diplopia is a complication of peribulbar anesthesia which could be persistent. The superior and inferior rectus muscle are especially vulnerable. Its occurrence may be technique - related and the incidence increases when hyaluronidase is not available.